Intranasal Niosomal In Situ Gel as a Promising Approach for Enhancing Flibanserin Bioavailability and Brain Delivery: In Vitro Optimization and Ex Vivo/In Vivo Evaluation - Usama A. Fahmy (Pharmaceutics, 2020)
Flibanserin (FLB) is a multifunctional serotonergic agent that was recently approved by the FDA for the oral treatment of premenopausal women with hypoactive sexual desire disorder. FLB is a centrally acting drug that has a low oral bioavailability of 33% owing to its exposure to the hepatic first-pass effect, as well as its pH-dependent solubility, which could be an obstacle hindering the drug dissolution and absorption via mucosal barriers. Thus, this work aimed at overcoming the aforementioned drawbacks and promoting the nose-to-brain delivery of FLB via the formulation of an intra-nasal in situ niosomal gel. The Box–Behnken design was employed to study the impact of Span® 85 concentration (X1), hydration time (X2), and pH of the hydrating buffer (X3) on the vesicle size and drug entrapment. The optimized formulation exhibited a spherical shape with a vesicular size of 46.35 nm and entrapment efficiency of 92.48%. The optimized FLB niosomes integrated into gellan gum-based in situ gel exhibited enhanced ex vivo permeation and improved plasma and brain concentrations after nasal administration in rats compared to raw FLB. These findings highlight the capability of the proposed intra-nasal FLB niosomal in situ gel to boost the drug bioavailability and to promote its direct delivery to the brain.